Peran Orang Tua dalam Meningkatkan Motivasi Belajar Peserta Didik Selama Pembelajaran Daring - Reza Rahmi Yeni; Mori Dianto; Wira Solina (Universitas PGRI SUMATERA BARAT, 2022)
This research is motivated by the problem of the role of parents in increasing students' learning motivation in bold learning. Like parents who don't care about their children's education, parents don't ask how the problems experienced by children in learning are brave. This study aims to describe the role of parents in increasing students' learning motivation. This type of research is descriptive quantitative research. The population of this study, namely all students of class VIII who came from junior high school 10 Padang opened 256 people. The sampling technique in this study used a proportional random sampling technique and obtained a sample of 72 students. The research instrument used a questionnaire/questionnaire. Techniques of data analysis using percentage analysis. The results showed that the role of parents in increasing students' learning motivation in bold learning was in the fairly good category. This research is definitely for BK teachers to be able to collaborate with parents and students in the learning process. Keywords: The role of parents, learning motivation, online learning